Autologous Blood Patch for Persistent Ascites Leak from Non-Closing Paracentesis Tracts - Khan, Nazia; Dushay, Kevin M. (Medical sciences (Basel), 2019)
Ascites, the fluid accumulation in the peritoneal cavity, is most commonly seen in patients with end-stage liver disease (ESLD). Evaluating ascites or providing symptomatic relief for patients is accomplished by performing a paracentesis. Ascites leak from a paracentesis site can be a complication of the procedure and is associated with increased morbidity. Currently, the best options for these patients include medical management or surgical abdominal wall layer closure. Utilizing a blood patch provides an alternative approach to managing such patients. A two-center prospective case series was performed evaluating the efficacy of the blood patch in patients with significant persistent ascites leak following a paracentesis. About 30 mL of the patients’ peripheral blood was used for the blood patch. Subjects were recruited over a period of one year and followed for 30 days after the procedure. A total of six patients were recruited for this study. Subjects underwent placement of autologous blood patch at the site of the ascites leak and 100% had resolution of the leak within 24 h. None of the subjects developed any complications of the procedure. This study shows that an autologous blood patch is an effective, low-risk treatment method for ascites leaks following a paracentesis. It is a simple bedside procedure that can reduce morbidity in patients with end-stage liver disease.